Turn Taking Strategies in Loukgolf’s English Room Talk Shows - Kassima Thainaphriao; Yesika Maya Ocktarani; Yunita Nugraheni (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
As long as people live in society, communication serves their vital need to convey their messages in the conversation. In doing conversation, speakers speak to each other in a certain order. It is called turn-taking in conversation. Turn-taking is an important aspect of conversation to get a smooth conversation. As a result, one must be understood and be aware of the techniques. However, a conversation sometimes does not run smoothly. In this situation, there might be something disturbing in the process of conversation. Therefore, an irregularity occurs that caused the conversation not to run well or might be cut off. Irregularity in conversation happens for certain purposes and the researcher aims to find out the form and the reason for irregularities performed by the host and the guest in “Loukgolf”s English room” talk show. To answer the problem, this research uses descriptive qualitative method. In analyzing the data, the researcher uses Natalia and Subekti’s theory to classify turn taking strategies and uses a system symbol from Jefferson and Cutting to represent the form of turn taking in transcribing the conversation. Based on theory there are four types of turn taking strategies. They are taking the turn, holding the turn, yielding the turn, and turn taking irregularities. Based on data analysis, this talk show found 79 turn taking strategies that categorize as regular 45 data consist of 19 taking the turn, 8 holding the turn, and 18 yielding the turn while the irregularities 34 data consist of interruption 18 data, and overlap 16 data. In addition, the researcher found 6 reasons of turn taking irregularities those are 4 asking for clarification, 1 asking for help, 2 rejection, 9 completions, 3 showing urgency, and 2 correcting. Based on the result the researcher concludes that turn taking occurs in each conversation both regular and irregular either with positive reasons or negative reasons depending on the context.